Using Equipercentile Equating to Link Scores of the CBCL and SDQ in Residential Youth. Issue 1 (2nd January 2021) - Stevens, Amy L.; Ho, Kai Yin; Mason, W. Alex; Chmelka, Mary B.
ABSTRACT: In data-driven residential care settings, it is sometimes necessary to change an established assessment tool due to cost and respondent burden. However, accurate assessment of youth functioning over time or across samples can be compromised when different assessments are used. Hence, the ability to crosswalk between assessments is important. The Child Behavior Checklist (CBCL) and Strengths and Difficulties Questionnaire (SDQ) screen for similar attributes and are highly correlated. The SDQ is shorter and free and can be an alternative to the CBCL. This study links the CBCL and SDQ total problem scores in a sample of 284 high-risk youth in a residential care facility, using equipercentile equating. Youth had both assessments completed on them concurrently by caregivers. The "equate" package in R Studio was used to conduct the analysis. Concordance tables were created for crosswalks from CBCL to SDQ and vice versa. Results showed linked scores that were consistent when equating from each assessment to the other. The concordance tables can serve as a comparison tool between total problem scores of each assessment. In particular, they could be a resource for residential care providers and researchers considering a switch from the CBCL to the SDQ as a resource-effective alternative.